Randomised study within a trial (SWAT) to evaluate personalised versus standard text message prompts for increasing trial participant response to postal questionnaires (PROMPTS) - Lucy Cureton (Trials, 2021)
Abstract Background Use of a person’s name in a text message has been shown to be effective in instigating behaviour change. We evaluated the effectiveness of a personalised text message (including the recipient’s name) versus a standardised text message for prompting a response from trial participants to complete and return postal follow-up questionnaires. Methods Using a randomised study within a trial (SWAT) embedded within the host GRASP (Getting it Right: Addressing Shoulder Pain) trial, participants who provided a mobile telephone number were randomised (1:1) by a central computer system to receive either (1) a personalised text message which included their name or (2) a standard text message. Text messages were sent by the trial office on the same day as the 6-month GRASP follow-up questionnaire. The primary outcome was questionnaire response rate, defined as the proportion of 6-month GRASP follow-up questionnaires returned by participants. Secondary outcomes included time to response, the proportion of participants sent a reminder follow-up questionnaire, and cost. Results Between March 2017 and May 2019 (recruitment period for GRASP trial), 618 participants were randomised to a personalised (n = 309) or standard (n = 309) text message and all were included in the analysis. The overall questionnaire response rate was 87% (n = 537/618); 90% (n = 277/309) of participants responded in the personalised text message group compared to 84% (n = 260/309) in the standard text message group (relative risk (RR) 1.07; 95% CI 1.00 to 1.13). Participants randomised to receive the personalised text message were more likely to return their initial postal questionnaire than those who received the standard text message (n = 185/309; 60% vs. n = 160/309; 52%) (RR 1.16; 95% CI 1.00 to 1.33); this represents an absolute percentage difference between intervention groups of 8%. Post hoc subgroup analysis showed that males under 65 years were the group most likely to return their initial questionnaire if they received a personalised text message. Conclusion Overall, participants who received a personalised text message were more likely to return their questionnaire than those who received the standard text message. Trial registration GRASP Trial ISRCTN16539266 ; SWAT Repository ID 35